Menumbuhkembangkan Lembaga Keuangan Mikro Syari’ah (Baitul Maal wa Tamwil) di Pulau Bengkalis - Nurmahadi Nurmahadi; Christina Tri Setyorini (LPPM ISNJ Bengkalis, 2019)
The emergence of sharia accounting and the prohibition of transactions that contain elements of usury is an order from Allah contained in the Qur'an and Hadith. These commands and prohibitions certainly contain benefits for mankind on earth, especially in muamalah activities. This study discusses the role of Baitul Maal wa Tamwil and how to grow and develop Baitul Maal wa Tamwil on Bengkalis Island through qualitative studies. The majority Muslim community and upholds Islamic spiritual values become the main capital to develop Baitul Maal wa Tamwil on Bengkalis Island. This condition, of course, is driven by the existence of Islamic economic colleges which produce qualified human resources in the field of accounting and Islamic economics. So that the benefits of Islamiyah can preserve human life on earth, namely preserving religion, preserving souls, preserving reason, preserving offspring and protecting property.